Investigation of human bocavirus in pediatric patients with respiratory tract infection - Ayfer Bakir; Nuran Karabulut; Sema Alacam; Sevim Mese; Ayper Somer; Ali Agacfidan (Journal of Infection in Developing Countries)
Introduction: Human bocavirus (HBoV) is a linear single-stranded DNA virus belonging to the Parvoviridae family. This study aimed to investigate the incidence of HBoV and co-infections in pediatric patients with symptoms of viral respiratory tract infection.